Das konvivialistische Manifest Für eine neue Kunst des Zusammenlebens (herausgegeben von Frank Adloff und Claus Leggewie in Zusammenarbeit mit dem Käte Hamburger Kolleg / Centre for Global Cooperation Research Duisburg, übersetzt aus dem Französischen von Eva Moldenhauer) - Les Convivialistes (X-Texte zu Kultur und Gesellschaft, 2014)
Global phenomenons like climate change, poverty, terrorism, or financial crises suggest thinking about changed forms of coexistence and perception. Many movements, initiatives, and groups are currently searching for alternative ways. They all share a yearning for a new art of living together (con-vivere). Convivialism means exploring possibilities for people to provide for each other and at the same time take care of nature, albeit without avoiding legitimate conflicts. The globally discussed manifesto by renowned authors clarifies: This can only succeed within a social order that invokes a joint humanity, principles of joint socialization, the principle of individuality, and acceptance of creative opposition.